Klasifikasi Citra Buah Catur Menggunakan Metode Klasifikasi Random Forest - Darrin, Eugenio; Karyawati, Anak Agung Istri Ngurah Eka (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 2 (2025): JNATIA Vol. 3, No. 2, Februari 2025, 2025)
Chess is known worldwide as an activity that is both considered a sport and a game alike, and yet it is also a way to develop the mind of people so that it might be sharper. In the game of chess there exists multiple types of chess pieces that are designed to be easily differentiated, and yet with the changing of time these differences might be reduced due to artistic reasons. Because of the reasons stated above that this research is conducted, which is to classify the multiple types of chess pieces so that beginner players might be able to differentiate them easily while playing a game of chess. The classification method that is proposed to be used in this research is still in the most basic knowledge and purposed to peak interest towards other researchers in using random forest classification in this topic